Espaços educativos: avanços e desafios para a cultura dos direitos humanos - Pelegrinelli, Gisela (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation deals with a relatively new theme in Brazilian education - human rights. In view of this perspective, since educational institutions are places of coexistence with diversity, the reasons for this theme are based on the principle that higher education helps prepare the student for the job market and performs the entire qualification process in the technical area, Interests of capitalism. However, there is a lack of a humanized view of life, a critical view. In this perspective, this dissertation is about a Case Study of the academic spaces of a Higher Education Institution – IES private the West Center. The question of study is How do the practice and experience of the Culture of Human Rights appear in the educational spaces? In methodological terms, the development of this research was qualitative of exploratory and descriptive nature using as a strategy the Case Study as a technique for data collection and Content Analysis of documents and other empirical materials in order to reach the results made possible by the dimension of the research. From the results obtained, it is verified that the IES studied recognizes the importance of the implementation of Education in Human Rights, however, has not yet found the way to discuss and, above all, to think of the Institution not as an educational space in which the Culture of Rights Humans are discussed in norms and decrees, but space in which this Culture is produced and experienced.
Keywords: Educação em direitos humanos; Educação superior; Espaços educativos; Cultura dos direitos humanos; Education in human rights; College education; Educational spaces; Culture of human rights; ACCNPQ::Ciências Humanas::Sociologia